2020
DOI: 10.1364/josab.381433
|View full text |Cite
|
Sign up to set email alerts
|

High gain in a dual-pass rod-type fiber amplifier

Abstract: Single-pass amplification using rod-type fibers has become a common route to pulsed laser sources around 1030 nm with high average and peak power. Average-power scaling is currently limited by the dynamic thermooptic phenomenon of "transverse mode instability." In comparison, double-pass amplifier configurations have not been extensively studied. Recent theoretical and experimental work has shown both static and dynamic mode degradation phenomena, including an unexpected nonlinear polarization rotation effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In contrast with the previous reported experimental research on rod-fiber ultrafast laser systems [21][22][23][24] , in our work, in addition to the general concerned average power, pulse energy, and pulse duration, we have also directed our research towards a beam pointing stability promotion technique. Therefore, we innovatively implemented a research work on improving beam pointing stability performance of high-power femtosecond fiber CPA laser systems, and presented a photonic crystal rod-based high-performance femtosecond fiber CPA laser source.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast with the previous reported experimental research on rod-fiber ultrafast laser systems [21][22][23][24] , in our work, in addition to the general concerned average power, pulse energy, and pulse duration, we have also directed our research towards a beam pointing stability promotion technique. Therefore, we innovatively implemented a research work on improving beam pointing stability performance of high-power femtosecond fiber CPA laser systems, and presented a photonic crystal rod-based high-performance femtosecond fiber CPA laser source.…”
Section: Introductionmentioning
confidence: 93%
“…The most successful attempt of MFA increment is the development and use of rod-type photonic crystal fibers. Exceptional performances in terms of average power and pulse energy have been demonstrated using photonic crystal rod [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distributions of the three TMI peaks above 100 Hz show the same dynamics with different variations. A recent work regarding dual-pass rod-type fiber amplifiers [22] has shown that vectorial modes are needed to fully describe the mode properties of these large core rods, but in this work we use the LP-modes for simplicity. All the TMI fluctuations in Fig.…”
Section: Application On Experimental Datamentioning
confidence: 99%